2019
DOI: 10.1128/iai.00243-19
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptors 2 and 4 Modulate Pulmonary Inflammation and Host Factors Mediated by Outer Membrane Vesicles Derived from Acinetobacter baumannii

Abstract: Pneumonia due to Gram-negative bacteria is associated with high mortality. Acinetobacter baumannii is a Gram-negative bacterium that is associated with hospital-acquired and ventilator-associated pneumonia. Bacteria have been described to release outer membrane vesicles (OMVs) that are capable of mediating systemic inflammation. The mechanism by which A. baumannii OMVs mediate inflammation is not fully defined. We sought to investigate the roles that Toll-like receptors (TLRs) play in A. baumannii OMV-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 43 publications
0
41
0
Order By: Relevance
“…The role of TLR4 in inflammatory diseases has been extensively studied 19,20 . In addition, the increasing amount of evidence pointed out that TLR4 signaling can promote injury, inflammation, and pulmonary fibrosis in acute or chronic lung injury mice model 21–23 . Generally, TLR4 could specially recognize Gram‐negative bacteria, such as LPS.…”
Section: Discussionmentioning
confidence: 99%
“…The role of TLR4 in inflammatory diseases has been extensively studied 19,20 . In addition, the increasing amount of evidence pointed out that TLR4 signaling can promote injury, inflammation, and pulmonary fibrosis in acute or chronic lung injury mice model 21–23 . Generally, TLR4 could specially recognize Gram‐negative bacteria, such as LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have described the release of membrane blebs from different pathogens, as well as their effects in vitro or in vivo (Holst et al, 2009; McConnell et al, 2011; Stevenson et al, 2018; Zhang et al, 2018). Recently, Marion et al (2019), showed pulmonary inflammation and neutrophil recruitment as well as cytokine production in mice inoculated with Acinetobacter baumannii membrane blebs intranasally. Also, membrane blebs from Aeromonas hydrophila induced B and T cell activation and the production of TNFα, IL-1β, and stimulated peripheral blood mononuclear cells producing IL-8 (Avila-Calderón et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for the observed discrepancy is not clear but can be related to the differences in the LPS purity, the bacterial strains and the cells used in the studies. In addition, the pulmonary proinflammatory responses induced by intranasal inoculation of mice with A. baumannii OMVs were partially inhibited in TLR2-/- and TLR4-/- mice as compared to those of wild-type mice, further highlighting the important roles of those TLRs in A. baumannii -induced pulmonary inflammation in vivo (Marion et al, 2019 ).…”
Section: Host Innate Immune Responses To a Baumanniimentioning
confidence: 98%